From Stage to Screen The Legacy of Traditional Chinese Theatre in Chinese Martial Arts Cinema Soundtracks - Wang, Shuang (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Chinese martial arts cinema is held to be a synthesis drawing on artistic conventions of traditional Chinese theatre. Film sound and music perform as the legitimate heirs of some of the aesthetic ideas and norms of traditional Chinese theatre. This book critically examines the history of this under-explored field of inquiry from a theoretically comparative perspective, demonstrating that the musical codes drawn from traditional theatre are a constantly changing component integral to Chinese martial arts cinema. It explores the interaction between traditional Chinese theatre and Chinese martial arts cinema in how the musical codes of the former have shaped the aesthetics of the latter uniquely. This departs from conventional existing studies that focus on "adaptation." The book's historical and theoretical approach connects film, theatre and music, and re-defines the status of distinctive domains of filmic expression, grounding theatre as the pivot - or "hinge" - of film aesthetics. The book proffers this unique angle of research to rethink and re-imagine film sound and audiovisual synchronisation. Primarily intended for scholars in Chinese cinema, film music, Chinese theatre and visual culture, this monograph also presents introductory and comprehensive material for undergraduate and graduate-level courses in film and media studies, film music, Chinese cinema, and Chinese theatre.
Introduction -- Chapter 1: Musicking The Chinese Martial Arts Cinema -- Chapter 2: Hearing the Theatre Through Four Moods -- Chapter 3: The Politics of Bodily Rhythm in Raining in the Mountain -- Chapter 4: The Drum Beat and its Diegetic Contextualization in Red Cliff II -- Chapter 5: Music and Slow Motion in the Banquet -- Chapter 6: Conclusion.
Keywords: Motion pictures -- Asia; Music; Theater -- History; Motion pictures; Music -- Philosophy and aesthetics; Asian Film and TV; Music; Theatre History; Film Theory; Philosophy of Music